Nitrogen, phosphorus and potassium status of rice co-planted with a novel phytoremediator, Marsilea minuta L. (Bangladesh Journal of Agricultural Research, 2018)
A pot experiment was carried out to assess the effects of arsenic and aquatic fern (Marsilea minuta L.), when applied as a phytoremediator, on the nutrient content (nitrogen, phosphorus, and potassium) of rice. Two sets of pot experiments were conducted in the net house on rice (Oryza sativa L.) together with aquatic fern (M. minuta) and on aquatic fern (M. minuta) alone where soils were treated with 1 mg/L As-solution at 80% arsenite and 20% arsenate. No significant difference was found in the nitrogen, phosphorus, and potassium concentrations of rice, in the absence of arsenic, whether grown in the presence of M. minuta or not. The uptake of total nitrogen, phosphorus, and potassium was found to be 36%, 23%, and 22% more, respectively in rice plants treated with M. minuta and arsenic over the control treatment, although the results were statistically insignificant. However, a significant negative relationship was found between arsenic and root nitrogen (P-value of 0.0017) when grown together with arsenic and M. minuta. A significant positive relationship was found between arsenic and shoot phosphorus (P-value of 0.0025) as well as arsenic and shoot and root potassium (P-values were 0.0045 and 0.0115, respectively). The results indicate that Marsilea minuta might be used as a phytoremediator of As together with rice plants.Bangladesh J. Agril. Res. 43(2): 211-218, June 2018